Are field boundary hedgerows the earliest example of a nature-based solution? - Collier, Marcus (My University, 2021)
The arrival of the phrase nature-based solutions into the lexicon of academics, planners, managers and policy makers in recent years has sparked a heated debate as to the effectiveness of using nature as a viable solution for mitigating the impacts of anthropogenic environmental change. One of the difficulties of evaluating the potential efficacy and impact of nature-based solutions is that it is believed that there is little evidence by way of a precedent or long-term successful examples. Much literature exists on the subject of designing with nature to provide multi-functional green infrastructure, connectivity in the landscape, and ecosystem service provision. Indeed, in the opinion of many, the nature-based solution approach appears to synergise research into green infrastructure, ecological connectivity and ecosystem service provision for building climate-related resilience. However, when a nature-based solution has been specifically selected over, say, an engineered solution the literature is rather less clear. So, decision-makers may find it necessary to rely on less reliable sources of impact evidence. This paper argues that field boundary hedgerows may be considered to be exemplars of a nature-based solution, one that was planned, designed, perfected and mainstreamed at a landscape scale, that was specifically selected over a non-nature-based solution, and one that is still in providing solutions and co-benefits today. Therefore, hedgerows may provide some perspective into the potential or emergent co-benefits that the current nature-based solution approach seeks to provide.
Keywords: Hedgerow; Nature-based solutions; Co-benefits; Field boundaries; Smart & Sustainable Planet; NATURE-BASED SOLUTIONS; field boundaries; field boundary; hedgerow; hedgerow ecology; hedgerows; Environment and housing; Policy